Cambridge Key English test 1 (Cambridge University Press, 2003)
These past examination papers provide the most authentic exam preparation available. They allow candidates to familiarise themselves with the content and format of the examination and to practise useful examination techniques. These papers follow the March 2004 revised exam specifications. A Student's Book 'with answers' is also available, containing a comprehensive section of keys and recording scripts, making it suitable for self-study